Participatory sensing and education: Helping the community mitigate sleep disturbance from traffic noise. Issue 4 (28th October 2014) - Ong, Kok-Leong; Leao, Simone; Krezel, Adam
Abstract : Purpose: – This paper aims to present a project in Australia, where participants use smartphones to measure the level of traffic noise in their homes. Through the data collected, participants learn if they are subjected to sleep disturbances and, if so, understand how they can manage the issue to protect their health. The project also has a secondary purpose: the local council would like to engage its community through the exercise and be seen as acting on the community's problems. Design/methodology/approach: – The approach taken was the development of a mobile app call 2Loud? that turns the smartphones of participants into noise sensors with accuracies comparable to professional sound-meters. The data collected are analyzed by environment and acoustic experts, and personalized feedback, in the form of mitigation strategies, is then provided. The strategies are delivered through the app to allow participants to share within the community and hence, propagate the solution to non-participants. Findings: – Participants who are technologically literate find a sense of empowerment as a result. They confirmed the importance of "closing the loop" with the feedback they received after their voluntary data collection effort. They also reported some sense of satisfaction with the technology as an interim solution and noted the council's creative approach. Originality/value: – This project first showcases how a participatory setup could be extended to create a "closed-loop" feedback system that further empowers its users. It is also a case example of how an organization could engage and manage its stakeholders' expectations through innovative use of participatory sensing systems.